Cognitive-Behavioral Treatment of the Posttraumatic Stress Disorder in a case of child rape - Guerra V., Cristóbal; Plaza V., Hugo (Revista de Psicología, 2009)
This article describes the treatment of a female child with posttraumatic stress disorder as a result of rape. This treatment integrates systematic desensitization, relaxation, control of thought, and psychoeducation. This treatment attempted to reduce intrusive symptoms, avoidant and increased physiological activation, characteristic of this disorder. To measure the effects of the intervention, was recorded the anxiety levels of the female child with scale units subjective anxiety (SUDS, Wolpe, 1958). The results indicate a gradual reduction of symptoms to reach minimum levels at nine weeks. These results are maintained in the follow-up weeks, months and two years after treatment ended. Finally, the theoretical and clinical implications of these results arediscussed.